Analisis Pendidikan Karakter Berbasis Religius Melalui Pembiasaan di SD Yimi Full Day School Gresik - Mudliatul Ilmiyah; Rudi Umar Susanto; Akhwani Akhwani; Suharmono Kasiyun (FKIP, Universitas Palangka Raya, 2024)
Increasing modern knowledge, technology and information presents a number of challenges for Indonesia. The character of the nation's children will deteriorate if it is not balanced with a solid foundation in moral principles and standards. The implementation of religious-based character education through habituation is very important to develop in order to form a personality that has good morals. This study aims to describe and analyze the implementation and supporting factors as well as inhibiting factors of religious-based character education through habituation at SD YIMI Full Day School Gresik. This research is a qualitative descriptive research with principals, teachers and students as research subjects. Data collection techniques in this study were in the form of observation, interviews and documentation. The results of this study indicate that religious-based character education through habituation at SD YIMI Full Day School Gresik is carried out through routine habituation activities, spontaneous habituation, exemplary habituation and fostering attitudes and activities according to religious indicators and evaluation. In addition, there are also supporting factors in its implementation such as teacher support, parental cooperation, school facilities. As for the inhibiting factors such as the child's own will, lack of support and awareness of parents, teacher factors, and colleagues.